Pertanggung Jawaban Notaris/Ppat Terhadap Pembatalan Aktanya oleh Pengadilan (Studi Putusan Nomor 250/Pdt.G/2015/Pn.Mdn) - Syaiful Hakim Siregar; Citra Ramadhan; M. Yusrizal Adi Syahputra (JUNCTO: Jurnal Ilmiah Hukum, 2022)
The purposef this research is how ti know the factors that cause the cancellation of the sale and purchase agreement deed caused by the authority of the Notary/PPAT, the responsibility of the Notary/PPAT for the cancellation of the deed he made, the legal consequences of the cancellation of the sale and purchase agreement deed by the court.The type of research in this thesis is normative juridical with descriptive analysis. The approach method used is the statutory approach. The factor that causes the cancellation of the Sale and Purchase Agreement Deed caused by the authority of a Notary/PPAT is if it violates the obligations as referred to in Article 16 paragraph (1) letter i, Article 16 paragraph (1) letter k, Article 44, 48, 49, 50 and 51 UUJN. The Notary/PPAT's responsibility for the cancellation of the deed he made in this case lies with the parties who made the deed. If there is a default or unlawful act between the parties, then the notary as the maker of the deed cannot be held accountable. Legal Consequences of the cancellation of the Sale and Purchase Agreement Deed by the Court Number 06 dated 04 August 2010 resulted in the result that all objects and persons were restored to the condition before the agreement was made. This means that the legal action contained in the deed does not have binding legal force between the parties who made it.